Collective in the Classroom: Creating Theatre in Secondary School Collaboration Projects - Lang, Linda (Theatre Research in Canada / Recherches théâtrales au Canada, 2007)
This school-based study explored how two intact classroom groups of students engaged with their drama teachers to collectively create original theatre for outside audiences. Two and one half months spent in a grade-ten classroom and four months in a grade-eleven classroom in two different schools yielded descriptive data drawn from classroom observation notes, documents, and interviews with ten students from each classroom group. Descriptive categories identified through preliminary analysis of data include group creative process, collaborative relationships, and evidence of theatre arts discourse. This paper explores how teachers and students understood their collaborative work as theatre. Résumé Cette étude en milieu scolaire porte sur deux classes d’élèves qui se sont engagés en compagnie de leurs enseignants d’art dramatique dans un projet de création collective présentée publiquement. Nous avons passé deux mois et demi auprès d‘une classe de dixième année et quatre auprès d‘une classe de onzième année, ce qui nous a permis de recueillir des données à partir d’observations, de documentation écrite et d’interviews réalisées auprès de dix élèves de chacune de ces classes. Les catégories que nous avons dégagées dans l’analyse préliminaire des données ont porté sur le processus de création du groupe, la collaboration entre les élèves et le discours théâtral. Cet article démontre la façon dont les enseignants et les élèves collaborent à un travail théâtral.